STATISTICAL ANALYSIS AND CASE INVESTIGATION OF FATAL FALL-FROM-HEIGHT ACCIDENTS IN THE CHINESE CONSTRUCTION INDUSTRY - Kang, Liangguo (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
A fall-from-height accident is considered a major leading cause of construction fatalities. The analysis of accident characteristics could offer effective guidance to the construction industry to prevent falls from heights. By using accident statistical analysis and typical case investigation, this study indicates the basic pattern and reviews in detail the conditions of a fall-from-height incident in China. The result shows that more fatal fall-from-height accidents occur from 10 a.m. to 11 a.m. and 3 p.m. to 4 p.m. Accidents on weekdays are nearly as many as on weekends. The lowest incidence month is February. Accidents resulting in one death take most of the total. Furthermore, not fastening a safety belt is among the leading reasons workers die after falling from heights. Victims in fall-from-height accidents are mostly male workers. Fall heights are most often less than 15 meters. This study serves to alert construction safety policymakers to diagnose the current state of fall-from-height accidents and provides a targeted direction for improving the safety record of work at height.